Corporate Social Responsibility, Good Corporate Governance, dan Nilai Perusahaan: Kinerja Keuangan sebagai Mediator - Rian Surachmad; Umu Khouroh (Jurnal Bisnis dan Manajemen, 2020)
This study purpose to examine the impact of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) on Firm Value with the mediator variable is Financial Performance. The samples used were 15 companies included in The Indonesia Most Trusted Company on Investors and Analysts Assessment Survey. The analytical method used the path analysis and hypotheses testing used SEM-PLS method. The results showed that CSR and GCG do no direct impact on firm’s value, on the contrary it had a positive impact on financial performance. Another finding is that financial performance has a direct effect on firm value thereby indicated the role of fully mediation in the relationship between CSR and GCG with firm value. For companies included in the group of The Indonesia Most Trusted Companies on Investors and Analysts Assessment Survey, the expansion of CSR and GCR information further strengthens the image that has an impact on increasing firm value. This empirical evidence reinforces the argument that companies need to do CSR and GCG to drive performance improvements which in turn will affect the firm value.